2011
DOI: 10.1080/01904167.2011.536878
|View full text |Cite
|
Sign up to set email alerts
|

Yield and Yield Components of Upland Rice as Influenced by Nitrogen Sources

Abstract: and urea are main sources of nitrogen (N) for annual crop production in developing countries. Two greenhouse experiments were conducted using ammonium sulfate and urea as N sources for upland rice grown on a Brazilian Oxisol. The N rates used were 0, 50, 100, 150, 3000, and 400 kg N kg −1 of soil. Yield and yield components were significantly increased in a quadratic fashion with increasing N rate. Ammonium sulfate X urea interaction was significant for grain yield, shoot dry matter yield, panicle number, plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
71
3
21

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(106 citation statements)
references
References 13 publications
11
71
3
21
Order By: Relevance
“…Similar results were obtained by Fageria et al (2011), working with upland rice. These authors observed higher plant height when using ammonium sulphate compared to urea at low N rates.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Similar results were obtained by Fageria et al (2011), working with upland rice. These authors observed higher plant height when using ammonium sulphate compared to urea at low N rates.…”
Section: Discussionsupporting
confidence: 76%
“…In Brazil, upland rice is sown mainly in Cerrado regions (Fageria & Baligar, 2005), where the soils are characterized by low natural fertility, high exchangeable aluminum, low organic matter content, low phosphorus availability and almost exclusive dependence of rainfall to supply the crop water requirements (Fageria, Moreira & Coelho, 2011;Fageria, Carvalho & dos Santos, 2014). Therefore, the yield of upland rice is low, contributing with only 41% of Brazilian production, despite having more than 60% of rice cultivation areas in Brazil (Alvarez, Crusciol & Nascente, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…No entanto, um dos grandes problemas do arroz de terras altas, quando se utilizam cultivares do tipo tradicional, ou do tipo intermediário, e se empregam doses elevadas de adubação, notadamente a nitrogenada, acompanhadas por práticas como a irrigação por aspersão, é o aumento da altura e, consequentemente, o acamamento de plantas (Soares et al, 2003;Nascimento et al, 2009;Fageria et al, 2011;Crusciol et al, 2012).…”
Section: Introductionunclassified
“…The high rice grain yield on fallow straw may be due to the fact that rice is a crop that has slow initial growth and that shows great sensitivity to competition with other plants (Menezes et al, 2001;Fageria et al, 2011). Thus, the proper management of plants (weeds) and the desiccation process have favored the full development of culture without competition.…”
Section: Resultsmentioning
confidence: 99%